Adherence to the Mediterranean diet and frequency of food consumption in high school students in Valencia - Spain - Pineda-Erazo, Carolina; Caicedo-Jaramillo, Carla; Mejía, Alirio; Ordoñez-Araque, Roberto (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction: Adolescence represents a crucial developmental stage for addressing and modifying eating patterns that may contribute to the prevalence of overweight and obesity. Objective: The aim of this research was to assess adherence to the Mediterranean diet (AMD) and the frequency of food consumption among secondary school adolescents in Valencia. Method: The PREDIMED questionnaire was utilized to evaluate AMD, in conjunction with a food consumption frequency questionnaire administered to a cohort of 166 students aged 12 to 17 years. Results: The primary findings of the study reveal that AMD is unrelated to weight or sex, with a higher percentage of normal-weight adolescents exhibiting high AMD. Conversely, there are instances of overweight students with high AMD and obese students with low AMD. The high AMD cohort tends to consume fruits and vegetables only 0 to 2 days a week, while dairy products are consumed 6 to 7 times a week. In contrast, the low AMD group consumes nuts, legumes, fruits, and vegetables 3 to 5 times a week. Both groups demonstrate a low daily intake of foods high in sugar and fat, along with a similar consumption frequency of cereals, starch, and tubers, with a higher representation of 3-5 times per week. Conclusion: The findings suggest that a high AMD does not necessarily correlate with good health. Other variables, such as dietary food frequency, play a significant role in determining weight for age. Similarly, a low AMD in conjunction with a diet rich in healthy foods can contribute to good health in students.